Increase of geomorphological risks in the urban space of Sarajevo as a consecuence of the process of suburbanisation and policies of neoliberalisation - Martín-Díaz, Jordi (2017)
In May 2014, the rainfall associated with the deep low pressure system called Tamara caused severe flooding and numerous landslides in the Western Balkans region, also reaching the city of Sarajevo (capital of Bosnia and Herzegovina). In this episode hydrological and geomorphological hazards affecting a significant number of urban and suburban areas built in the Bosnian capital since the end of the war were evidenced. From an observational and ethnographic work carried out between 2010 and 2013 and operational support of GIS, this paper aims at highlighting the unsustainable direction of its built environment. This has been caused by the densification occurred in floodplain as well as the intense suburbanisation process of the slopes. Both processes are respectively produced by the international policies promoting a neoliberal urban development and the need of people refugeed in Sarajevo to stabilise their situation in the city after the war.